2022
DOI: 10.3389/fpubh.2022.982330
|View full text |Cite
|
Sign up to set email alerts
|

How slack resource affects hospital financial performance: The evidence from public hospitals in Beijing

Abstract: BackgroundBeijing is a city with high concentration and congestion of quality medical resources in China. While moderate slack seems to be beneficial to the improvement of medical quality. The actual relationship between hospital slack resources and their performance deserves further exploration. The study aims to analyze the slack resources of public hospitals in Beijing and investigate the relationship between slack and hospital financial performance. Finding a reasonable range of slack to optimize resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…To some extent, slack resources are conducive to the improvement of financial performance (C. Chen et al, 2022). The better a company's financial performance, the more willing it is to spend on CSR (Nguyen et al, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, slack resources are conducive to the improvement of financial performance (C. Chen et al, 2022). The better a company's financial performance, the more willing it is to spend on CSR (Nguyen et al, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…To some extent, slack resources are conducive to the improvement of financial performance (C. Chen et al, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The specificity of these hospital administrations and the particular geographical features of Beijing may have led to a biased selection of respondents that is not reflective of all medical staff. While prior studies of the same 22 hospitals have shown that this selection is feasible and scientific ( Chen et al, 2022 ) and the large sample size of >2,000 respondents helped to increase the representativeness of the current study, potential bias cannot be ruled out. Subsequent studies will need to include primary care institutions, other hospital types, and additional geographic areas, to gain a more comprehensive understanding of the ID of medical staff.…”
Section: Limitationsmentioning
confidence: 99%